PENGGUNAAN METODE HYPNOTEACHING MENGGUNAKAN PERMAINAN KARTU HEBAT TERHADAP KEMAMPUAN PERCAYA DIRI ANAK USIA 5-6 TAHUN - bibah, habibah; Maulidiyah, Eka Cahya; Fitri, Ruqoyyah; Mas’udah, Mas’udah (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
The problem that is often faced by children is the ability of children's self-confidence which is still lacking, so it needs to be stimulated. One method that can be used to stimulate a child's self-confidence is the hypnoteaching method. The purpose of this study was to show whether there is an effect of the hypnoteaching method using great cards on the self-confidence of children aged 5-6 years. The research subjects were group B kindergarten children with a total of 38 children. Children's confidence instruments include: (1) Interacting with the teacher; (2) Express opinions in a simple way; (3) Make simple decisions; and (4) Demonstrating a willingness to appear in front of the class. The method used is a quantitative experimental research method. The experimental design used was quasi-experimental using a non-equivalent control group design. The tool used in this research is observation. In this research, data collection techniques used structured observation using observation sheets. Data analysis techniques used include normality test, homogeneity test and hypothesis testing using the Independent Sample T Test. Based on the calculation results, the significance value (2-tailed) is 0.000 <0.05, that Ha is accepted and Ho is rejected. So it can be seen that there is a significant effect of the hypnoteaching method using the Great Card game on the self-confidence of group B children. The treatment through the Hypnoteaching method using the Great Card game increases the child's self-confidence score, so that it can be said that the child's self-confidence can be stimulated by given positive suggestions and there is a gradual process of activity.